Spirometric indices in primary ciliary dyskinesia: systematic review and meta-analysis - Halbeisen, Florian S. (ERJ Open Res, 2019)
Primary ciliary dyskinesia (PCD) is a genetic, heterogeneous disease caused by dysfunction of cilia. Evidence is sparse and reports of lung function in PCD patients range from normal to severe impairment. This systematic review and meta-analysis of studies of lung function in PCD patients examines the spirometric indices of PCD patients and differences by age group and sex. We searched PubMed, Embase and Scopus for studies that described lung function in 10 or more patients with PCD. We performed meta-analyses and meta-regression to explain heterogeneity. We included 24 studies, ranging from 13 to 158 patients per study. The most commonly reported spirometric indices were forced expiratory volume in 1 s (FEV(1)) and forced vital capacity presented as mean and standard deviation of percent predicted values. We found considerable heterogeneity for both parameters (I(2)=94–96%). The heterogeneity remained when we stratified the analysis by age; however, FEV(1) in adult patients was lower. Even after taking into account explanatory factors, the largest part of the between-studies variance remained unexplained. Heterogeneity could be explained by genetic differences between study populations, methodological factors related to the variability of study inclusion criteria or details on the performance and evaluation of lung function measurements that we could not account for. Prospective studies therefore need to use standardised protocols and international reference values. These results underline the possibility of distinct PCD phenotypes as in other chronic respiratory diseases. Detailed characterisation of these phenotypes and related genotypes is needed in order to better understand the natural history of PCD.